Sustainable and effective Chitosan-based edible films incorporated with OEO nanoemulsion against apricots' black spot. (August 2022) - Guo, Shuangfeng; Li, Tingting; Chen, Ming; Wu, Caie; Ge, Xuemei; Fan, Gongjian; Li, Xiaojing; Zhou, Dandan; Mi, lin; Zhao, Xuran; Yang, Tianyou
Abstract: Black spot rot caused by Alternaria alternata is one of apricots' ( Prunus armeniaca L.) main postharvest diseases. This disease has caused considerable losses during fruit storage in recent years. This study aimed to produce a safe, convenient and commercially viable film material to preserve apricots by inhibiting the growth of Alternaria alternata . Oregano essential oil (OEO) has a good inhibitory effect on Alternaria alternata . In this study, OEO was added to chitosan-based films in the form of nanoemulsions acquired through ultrasonic emulsification to prolong its antifungal effect. The influence of the OEO concentration (2%, 4%, 6% (w/v)) and ultrasound time (0, 5, 10, 20, 30 min) on the stability and antifungal properties of the OEO nanoemulsions were investigated. Furthermore, the structure and properties of the chitosan-based edible films incorporated with OEO nanoemulsions (0, 0.2%, 0.5%, 1%, 1.5% v/v) were studied. Results revealed that the 4% (w/v) OEO nanoemulsion with 20 min of ultrasound treatment exhibited the best antifungal property and emulsion stability. The chitosan film incorporated with 1% (v/v) of 4% (w/v) OEO nanoemulsion (CS-1%OEO) significantly improved the antifungal properties in vitro . The incidence of apricot inoculated with Alternaria alternata in the presence of the CS-1%OEO film was 42.86% lower than that of control (without film) at three days, indicating the effectively controlled of black spot disease on apricots. Furthermore, the safety of the CS-1%OEO film was confirmed by the zebrafish model. The results obtained in the study showed the potential of the CS-1%OEO film in the disease resistance of apricots from the black spot caused by Alternaria alternata . Graphical abstract: Image 1 Highlights: Antifungal activity of the emulsion was dependent on droplet size and stability. Nanoemulsion-mediated delayed release of volatile compounds from the film matrix. The composite films showed great potential to resist black spot of apricot. The safety of the composite films were confirmed by zebrafish model.